ANALISIS SEKTOR EKONOMI UNGGULAN DI KOTA BATU TAHUN 2012-2018 - Nur Roni Faturohman; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi JIE, 2020)
Economic development in Batu City cannot be separated from economic growth, while economic development encourages economic growth and vice versa economic growth accelerates the process of regional development. This study aims to determine the leading economic sectors in Batu City in 2012-2018. The results of the study are based on a combined analysis of Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ) obtained as sectors that are classified as leading economies, namely agriculture, mining, and fisheries, air procurement, construction, wholesale trade and trade, supply accomodation, real estate and other services. Mainstay economic sectors are the manufacturing sector, electricity and gas procurement, as well as transportation and warehousing. Prospective economic sectors are the information and communication sector, financial services and insurance, government administration, education services, as well as health services and social activities. And the lagging economic sector is the mining sector, and corporate services. Using Shift-Share (SS) analysis, the contributing sector is growing fast and is being developed for the manufacturing, construction, wholesale and retail, transportation and warehousing sectors, transportation, information and communication, financial services, real estate, corporate services, education services and health services. While the results of the analysis using the Klassen Typology sectors that are classified as fast-moving and fast-growing are the construction sector, wholesale trade and trade, the supply of goods and beverages, communication and information, and other services.